Effect of supplementation with different dietary energy sources on semen quality in a cold-stressed boar model - Jiayi Li; Yujie Wu; Min Yang; Zhengfeng Fang; Lianqiang Che; Shengyu Xu; Bin Feng; Yong Zhuo; Jian Li; Lun Hua; De Wu; Yan Lin (Animal Biotechnology, 2025)
Cold ambient temperatures decrease semen quality. However, the effects of dietary energy sources on semen quality under cold stress conditions remain unclear. In the present study, purebred Yorkshire boars (572 days old) were fed diets supplemented with either fat (FAT), amino acid complex (AA), or dietary fiber beet pulp (BP) during the winter. The experiment was conducted for 84 days. Results showed that BP supplementation increased semen volume, sperm count, plasma immunoglobulin M level and the relative abundance of fecal norank_f_Erysipelotrichaceae (positively correlated with sperm viability), while decreasing the levels of interleukin-1β and lipopolysaccharide-binding protein (p < 0.05). AA supplementation increased sperm density, progressive motility, and sperm velocity during weeks 7–12 (p < 0.05), while no significant effect was observed during weeks 1–6. The relative abundance of fecal Lachnospiraceae_UCG-006 (positively correlated with sperm velocity) also was increased in the AA group. FAT supplementation had a minor effect on sperm progressive motility and average curvilinear velocity, which may be related to the increased relative abundance of fecal T2WK15B57 (negatively correlated with semen quality). In summary, daily supplementation with BP and AA improves sperm quality under cold stress conditions, likely through improvements in inflammation, immunity and intestinal microflora.